PERANCANGAN SISTEM APLIKASI UANG KAS BERBASIS WEB PADA SEKOLAH DASAR NEGERI (SDN) BABAKAN I - Alfan Putranto (CV. Multi Kreasi Media, 2024)
Along with the development of the current era which is getting easier and faster, of course, all things that still use manual techniques are increasingly being abandoned because they are considered no longer effective, with today's technology everything can be accessed easily and quickly, whether it's a matter of information or about other things. as well as in the case of recording cash, the research method used to create Web-based Cash Applications using the Waterfall Method. First introduced by Winston Royce around 1970 so it is often considered ancient, but is the most widely used model in Software Engineering (SE). ). This model takes a systematic and sequential approach. It is called the waterfall because the stages that are passed must wait for the completion of the previous stage and run sequentially. Ongoing cash income at school, as well as the difficulty of delivering information from the treasurer about various things, both expenditure and cash income to parents and teachers. After going through several stages the author concludes as follows: Application System for Recording Cash at SD Negeri Babakan 1 South Tangerang can assist in recording or reporting data about cash which is easier, faster and more accurate and data collection no longer needs to use manual methods which take a long time and require a lot of paper because it is computerized.